2014
DOI: 10.1159/000360752
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphisms rs1333040 and rs7865618 of Chromosome 9p21 and Sporadic Brain Arteriovenous Malformations

Abstract: Background: The chromosomal locus 9p21 is a novel genetic marker for a variety of cardiovascular and cerebrovascular diseases. In a recent study, we have demonstrated an association between the single nucleotide polymorphism (SNP) rs1333040C>T on chromosome 9p21 and sporadic brain arteriovenous malformations (BAVMs). Here, we extended our analysis to an additional SNP on chromosome 9p21 (rs7865618A>G) and increased our sample size including BAVMs from two different Italian neurosurgical centers. Methods: We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…[29] Interestingly, CDKN2B–AS1 is a non-coding RNA located within the CDKN2A–CDKN2B gene cluster on 9p21, the strongest genetic locus for cardiovascular diseases and linked to intracranial aneurysm. [32] More recently, the 9p21 SNP rs1333040 has been associated with BAVM,[15, 33] and replicated in our discovery cohort (Phase 1). However, this genetic association appears to be explained by the presence of BAVM-associated aneurysms.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…[29] Interestingly, CDKN2B–AS1 is a non-coding RNA located within the CDKN2A–CDKN2B gene cluster on 9p21, the strongest genetic locus for cardiovascular diseases and linked to intracranial aneurysm. [32] More recently, the 9p21 SNP rs1333040 has been associated with BAVM,[15, 33] and replicated in our discovery cohort (Phase 1). However, this genetic association appears to be explained by the presence of BAVM-associated aneurysms.…”
Section: Discussionsupporting
confidence: 53%
“…[10][11][12][13][14][15] Of these, 57 SNPs were successfully genotyped in the replication cohort (call rate >96.9%). Samples with >10% missing genotypes were excluded, resulting in 608 cases and 744 controls.…”
Section: Replication Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…SNP rs1333049 in CDKN2B-AS1 was located on chromosome 9p21.3, which was considered as the most widely and consistently replicated risk locus for cardiovascular and CDs. 29) Previous study showed that CDKN2B-AS1 polymorphism significantly associated with the risk of glioma by affecting the gliomagenesis. 35) The CDKN2B - AS1 polymorphism rs1333040 was located on the risk locus chromosome 9p21.3, and showed high linkage disequilibrium with rs1333049 (0.81≤r 2 ≤0.97) in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…I have read with interest a recent article in Cerebrovascular Diseases by Sturiale et al, entitled ‘Association between polymorphisms rs1333040 and rs7865618 of chromosome 9p21 and sporadic brain arteriovenous malformations' [1]. The authors analyzed single nucleotide polymorphisms (SNP) on the p21 locus of chromosome 9 in 206 patients with cerebral arteriovenous malformations (AVM), using 171 patients without intracranial vascular malformations as controls.…”
mentioning
confidence: 99%